USE OF GLIRICIDIA-ENRICHED LIQUID ORGANIC FERTILIZER FOR PRODUCTION OF CAISIM (Brassica juncea L.) - Alakhyar, Alakhyar; Fahrurrozi, Fahrurrozi; Widodo, Widodo; Sari, Dia Novita (University of Prof. Dr. Hazairin, SH, 2019)
Green biomass is one of major nutrient source and determines the quality of liquid organic fertilizer (LOF), including Gliricidia sepium (Jacq.) Kunth ex Walp. An experiment was conducted to study the effects of Gliricidia-enriched LOF on growth and yields of caisim, arranged in randomized complete design with three replicates. Treatments consisted of six LOF concentrations, 0%, 20%, 40%, 60%, 80% and 100%. Results indicated that concentration of gliricidia-LOF significantly influenced leaf greenness and shoot fresh weight, but not root to shoot ratio and shoot water content.  Concentrations of gliricidia-LOF increased leaf greenness and shoot fresh weight of caisim. The optimum concentration was 70.85% to produce weight of 73 grams caisim per plant. Root to shoot ratio was not significantly different. Although treatments did not affect shoot water content, all caisim water content was on average above 90 %.